A New Method for Static Measurement of Two Axles Vehicle Centroid Height - Fan, Xiaobin; Zhang, Mingyue (Recent Patents on Engineering, 2020)
Background: Vehicle centroid height is an important parameter in vehicle control systems. It plays an important role in vehicle roll stability and handling stability. At present, there are mainly static and dynamic measurement methods such as swing method, mass reaction method, marking method and so on. These static measurement methods often require a fixed suspension to make the measurement process time-consuming and laborious, and measurement errors will occur when the suspension is not fixed firmly, and it is impossible to measure the mass center position of spring-loaded mass and non-spring-loaded mass. Objective: Therefore, it is of great practical significance to study a high accuracy, low cost and fast measurement method of vehicle centroid height. We revised and summarized all patents relating to methods for estimating vehicle centroid height. And a new method of centroid measurement is designed in this paper. Methods: According to the change of tire flattening radius and suspension, the change of spring and non-spring mass center height when vehicle axle load changes, the method of delineation is used to calculate the change of tire flattening radius and suspension; According to the relationship between vehicle tilt angle and front and rear axle load, the principle of moment balance and the principle of mass balance, it determines the geometric relationship between the variables, and to take the moment of the contact point between the front wheel and the ground, the moment balance equation is established, and the height of the vehicle mass center, spring load and non-spring load mass center in the horizontal position of the vehicle are obtained. Results: This measurement method is different from the existing static measurement of vehicle centroid height, it does not need the fixed suspension, only need to measure several dimensions, we can avoid heavy labor and safety accidents brought by the fixed suspension, it can also reduce the measurement error caused by fixation, but also can draw the centroid location of the sprung mass and unsprung mass. The measurement method is simple, economical and accurate, and is widely applicable on two-axle vehicles. Conclusion: The purpose of this paper is to provide a static and accurate measurement method of vehicle centroid height, so as to solve the problem that the current static measurement method of vehicle centroid height needs fixed suspension, and measurement errors will occur when the suspension is not fixed properly, so it is impossible to measure the centroid position of spring-loaded mass and non-spring-loaded mass.
Keywords: unsprung mass